Generation of polycyclic aromatic hydrocarbons (PAHs) during woodworking operations - Bruschweiler, Evin D.; Danuser, Brigitta; Cong, Khanh H.; Wild, Pascal; Schupfer, Patrick; Vernez, David; boiteux, Philippe; Hopf, Nancy B. (Frontiers in Oncology, 2012)
Occupational exposures to wood dust have been associated with an elevated risk of sinonasal cancer (SNC). Wood dust is recognized as a human carcinogen but the specific cancer causative agent remains unknown. One possible explanation is a co-exposure to; wood dust and polycyclic aromatic hydrocarbons (PAHs). PAHs could be generated during incomplete combustion of wood due to heat created by use of power tools. To determine if PAHs are generated from wood during common woodworking operations, PAHs concentrations in wood dust samples collected in an experimental chamber operated under controlled conditions were analyzed. In addition, personal air samples from workers exposed to wood dust (n=30) were collected. Wood dust was generated using tree different power tools: vibrating sander, belt sander, and saw; and six wood materials: fir, Medium Density Fiberboard (MDF), beech, mahogany, oak and wood melamine. Monitoring of wood workers was carried out by means of personnel sampler device during wood working operations. We measured 21 PAHs concentrations in wood dust samples by capillary gas chromatographic-ion trap mass spectrometric analysis (GC-MS). Total PAH concentrations in wood dust varied greatly (0.24 – 7.95 ppm) with the lowest being in MDF dust and the highest in wood melamine dust. Personal exposures to PAHs observed were between 37.5-119.8 ng m-3 among workers during wood working operations. Our results suggest that PAH exposures during woodworking operation are present and hence could play a role in the mechanism of cancer induction related to wood dust exposure.